Open Disclosure Practices of Patient Safety Incidents in Indonesian Hospitals - Dhamanti, Inge; Rachman, Taufik; Wardahni, Rizka Kusuma (eJournal Kedokteran Indonesia, 2025)
Open disclosure of patient safety incidents in Indonesian hospitals is essential to improve transparency, foster trust, and enhance the quality of healthcare services. This study aims to analyze attitudes and barriers to the open disclosure of patient safety incidents in Indonesian hospitals. A descriptive quantitative research method was applied, involving 265 healthcare workers with at least 1 year of hospital experience at an Indonesian Hospital. Data collection was conducted via an online questionnaire over 2 weeks, recruited through convenience sampling, and analyzed descriptively. The findings reveal that most respondents believe that patients should be informed about safety incidents that affect them. Additionally, the majority of respondents agreed that ethically disclosing patient safety incidents is very important. However, the study results also indicate barriers to open disclosure, as many respondents believe that only serious patient safety incidents should be disclosed to patients. This perception is primarily driven by fears of losing their reputation, fear of penalties, and the belief that open disclosure may increase the risk of lawsuits. The results highlight the need for goverments' policies to address the identified barriers and to support the implementation of open disclosure in hospitals by strengthening institutional support and providing training programs to enhance patient safety culture in Indonesia.